Effect of Supplementation of Vegetable Oils in feed of broiler Rabbits - Arulmuthumathavan, M.; Ramesh, V.; Ramakrishnan, S.; Senthilkumar, S.; Sivakumar, K. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was conducted on 48 weaned Soviet Chinchilla rabbits to evaluate the effect of supplementation of vegetable oils with respect to growth and reproductive performance. The rabbits were divided into four groups of twelve each. First group (T1) fed on basal diet alone, second group (T2) fed on basal diet supplemented with rice bran oil @ 2 per cent level, third group (T3) fed on basal diet supplemented with palm oil @2 per cent level and fourth group (T4) fed on basal diet supplemented with both rice bran oil and palm oil each @ one per cent level. The result of the study reveals that rabbits fed basal diet with 2 per cent palm oil group (T3) had significantly (P
Keywords: Broiler Rabbits; Oil Supplementation; Performance; Economics